Policy Window as a Trapdoor: Rethinking the Multiple Streams Framework through the Defunding of U.S. Public Media - Hilde Van den Bulck; Christopher Ali; Jonathan Kropko (The International Journal of Press/Politics, 2026)
This article analyses the 2025 defunding of U.S. public media as a critical case to revisit Kingdon’s multiple streams framework (MSF). While MSF offers a useful heuristic for understanding policy change through the convergence of problem, policy, and political streams, its explanatory power is limited by assumptions of contingency, pluralism, and stakeholder inclusion. Under growing illiberalism, the “policy window” functioned less as an accidental opening than as a trapdoor, built through ideological persistence, institutional erosion and coordinated policy design. Drawing on critical discourse analysis of congressional hearings, executive orders, political communication, and media coverage, alongside survey data on public broadcasting system audiences, this study shows how conservative actors sustained a politicized definition of public media bias and institutionalized policy solutions. The survey highlights a disjuncture between audience trust and the construction of public media as a policy problem. Rather than spontaneous convergence, the case reflects coordinated restructuring of the public media system. More broadly, it suggests that MSF becomes less effective when stream independence is undermined by executive dominance and ideological alignment, requiring approaches that foreground power, discourse, and exclusion.